2008
DOI: 10.1016/j.jim.2008.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Engineering higher affinity T cell receptors using a T cell display system

Abstract: The T cell receptor (TCR) determines the cellular response to antigens, which are presented on the surface of target cells in the form of a peptide bound to a product of the major histocompatibility complex (pepMHC). The response of the T cell depends on the affinity of the TCR for the pepMHC, yet many TCRs have been shown to be of low affinity, and some naturally occurring T cell responses are poor due to low affinities. Accordingly, engineering the TCR for increased affinity for pepMHC, particularly tumor-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
67
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(67 citation statements)
references
References 61 publications
0
67
0
Order By: Relevance
“…Enhanced-affinity variants of the 3D TCR were generated using a T-cell display system, as has been previously described, 3 and selection was made with WT1/D b Ig DimerX (BD Biosciences) (supplemental Methods). Two enhancedaffinity complementarity determining region (CDR) 3a mutants were identified that bound the peptide/major histocompatibility complex (MHC) dimer independent of CD8: the Q103H mutant (3D-NYH) and the N101P, Q103Y mutant (3D-PYY) ( Figure 1A-B).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced-affinity variants of the 3D TCR were generated using a T-cell display system, as has been previously described, 3 and selection was made with WT1/D b Ig DimerX (BD Biosciences) (supplemental Methods). Two enhancedaffinity complementarity determining region (CDR) 3a mutants were identified that bound the peptide/major histocompatibility complex (MHC) dimer independent of CD8: the Q103H mutant (3D-NYH) and the N101P, Q103Y mutant (3D-PYY) ( Figure 1A-B).…”
Section: Resultsmentioning
confidence: 99%
“…2 In these cases, the affinity of such naturally occurring TCRs can be enhanced through in vitro directed evolution strategies as a means to increase the anti-tumor efficacy of the gene-therapy treatment. [3][4][5] Approaches to increase the affinity of tumor-reactive TCRs are predicated on the assumption that the thymus to some degree overprotects against self-reactivity, such that T cells expressing higheraffinity variants will be tolerated when transferred in vivo or that the extent of tissue injury or T-cell dysfunction resulting from recognition of normal tissues will be acceptable. Many tumor antigens that are candidates for therapeutic targeting are expressed at high levels during embryogenesis, but very low levels in adult tissues.…”
Section: Introductionmentioning
confidence: 99%
“…One recent and promising approach to overcome the issue of the intrinsically low-affinity of TCR to self-antigens has been to enhance the affinity of the TCR isolated from such T cells by mutagenesis of a and b receptor chains. Recent technological advances have facilitated elegant molecular and rational high-throughput genetic approaches to affinity enhance TCRs [33][34][35], and such efforts have resulted in the ability to reproducibly generate TCR with substantially higher affinities for target antigens [36]. An alternative strategy to enhance TCR affinity follows from observations of enhanced functional avidity and improved recognition of tumour cells following introduction of mutations that reduced N-glycosylation on TCR chains [37].…”
Section: T-cell Receptor Engineeringmentioning
confidence: 99%
“…The goal of using a TCR as a targeting moiety for a soluble immunotherapeutic has become plausible due to advances in engineering and directed evolution (reviewed in (Richman & Kranz 2007)) using techniques such as yeast surface display, phage display, or more recently, T cell display (Chervin et al 2008). Engineered receptors with 1000-fold or more increased affinity compared to their original, wild-type TCRs have been isolated, and the soluble forms of these TCRs bind to the targeted peptide-MHC with a high level of specificity (Chervin et al 2008;Holler et al 2003;Holler et al 2000;Li et al 2005b;Weber et al 2005).…”
Section: Affinity Considerations / Engineeringmentioning
confidence: 99%
“…Engineered receptors with 1000-fold or more increased affinity compared to their original, wild-type TCRs have been isolated, and the soluble forms of these TCRs bind to the targeted peptide-MHC with a high level of specificity (Chervin et al 2008;Holler et al 2003;Holler et al 2000;Li et al 2005b;Weber et al 2005). The higher affinities achieved for TCR binding to peptide-MHC (nanomolar and picomolar) are in the range of affinity-matured antibodies, and are thus sufficient to evaluate for their ability to serve as soluble therapeutics.…”
Section: Affinity Considerations / Engineeringmentioning
confidence: 99%